Programa de tutoría en directivos para la prevención de la drogadicción en la Institución Educativa Mariscal Oscar R. Benavides Iquitos 2019 - Panduro del Águila, Víctor Raúl (2021)
The research had as a question: What is the effect of the application of the mentoring program in principals for the prevention of drug addiction at the Mariscal Oscar R. Benavides Educational Institution, Iquitos, 2019? and as a general objective to evaluate the effect of the application of the mentoring program in principals for the prevention of drug addiction at the Mariscal Oscar R. Benavides Educational Institution, Iquitos, in 2019. The type of study was evaluative with a single-group quasi-experimental design. The sample was obtained through the non-probalistic method and consisted of 31 principals. The educational test was used as a technique for data collection, and the written performance test was the instrument. The written performance test instrument was subjected to expert judgment for its validity and reliability. Contrasting and testing of the hypothesis was done using the nonparametric Wilcoxon range test for paired or related samples. It is concluded that the implementation of the program has an effect because there is a significant improvement in the level of substance addiction prevention among the directors of the intervened educational institution, the same that has been verified in the inferential analysis, of the research, since in general results are obtained with p = 0.000 (p <0.000) and Z-KS = 0.351 before the intervention and after this p = 0.000 (p> 0.05) with Z-KS = 0.461. The program managed to improve the principal's personal, interpersonal and biopsychosocial dimensions to strengthen drug addiction prevention.